PROSPEK ADOPSI BANK SYARIAH DI KALANGAN CIVITAS AKADEMIKA UNISMA BEKASI - ., Isfandayani (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2016)
One of Sharia Institutions in Indonesia is Islamic Bank, which develops rapidly. Unisma does not make partership with Islamic Bank. This becomes my background toconduct research entitle: The Prospect of Islamic Bank Adoption in The Civitas Academica of Unisma Bekasi. This research uses qualitative method with descriptiveand comparison analysis. Researcher wants to know how deep Unisma Civitas Academica understands about Islamic Bank concept and the prospects if Unisma invitesIslamic Bank as its partner. The prospects comparise finance, peaceful and service side. In this research it would be explained about steps if Unisma would like to add Islamic Bank as its partner. The goal of this research is; The Unisma Civitas Academica have good understand about Islamic Banking. If Unisma makes partnership with Islamic Bank (adoption), there would be 3 goals to reach. Firstly, Unisma would obtain more profit (compared to that obtained from interest of the existing conventional bank of which the Unisma?s partnership and equivalent rate of Islamic Bank of 2015). Secondly, it would be peaceful since it would be free from ?riba? or interest system. Thirdly, Islamic Bank partnership is hopefully to be better, since Unisma parnership with conventional bank currently is not good. The procedures for Unisma to invite Islamic Bank as its partner are as follow: make comparison benefit research between conventional and Islamic bank intitutions, high level agreement conducted in management meeting, presentations from some Islamic Bank Institutions, the management selection among institutions and prepares infrastructures appropriate for their site plan building.